Kewajiban Nafkah Suami Terhadap Istri Bekerja Dan Kedudukan Harta Hasil Kerjanya: Analisis Perspektif Mazhab Empat Dan Hukum Positif Indonesia - Agung Taufik Wahyuda; Heri Firmansyah (Tabayyun : Journal Of Islamic Studies, 2026)
The development of women's roles in the economic field has given rise to various legal issues related to the concept of qiwamah and the status of a wife's assets in the household. This issue is important because there are differing views among Islamic scholars regarding the requirements and validity of maintenance, as well as differences in regulations between Islamic law and Indonesian positive law regarding the status of a wife's assets. This study aims to analyze a husband's maintenance obligations towards his working wife, understand the concept of qiwamah, and examine the status of the wife's assets earned from her work. This study is a normative legal study with a legislative, conceptual, and comparative approach analyzed qualitatively through literature review. The results show that all schools of thought agree that maintenance is a husband's obligation, although there are differences regarding the requirements, starting time, and amount of maintenance. Qiwamah is understood as a responsibility for leadership and protection within the family related to the obligation of maintenance, not as a form of domination. Furthermore, according to the four schools of thought, the wife's labor-earned assets remain the wife's personal property and do not eliminate the husband's maintenance obligations, except in the case of nusyuz. Under Indonesian positive law, such assets are in principle considered joint property, but individual ownership rights are still recognized. This research provides a more comprehensive understanding of the relationship between livelihood, qiwamah (charity), and the ownership of a working wife's property, as a basis for strengthening more contextual Islamic family law practices.